Comparison of pathologic changes in mammalian hosts infected with Schistosoma mansoni, S. japonicum and S. haematobium - Allen W. Cheever (Memorias do Instituto Oswaldo Cruz, 1987)
The hepatic, intestinal and cardiopulmonary lesions produced by Schistosoma mansoni, S. haematobium and S. japonicum in man and experimental animals often bear striking similarities but usually have distinctive features as well. These are often related to parasitologic differences. Thus S. japonicum and S. haematobium lay their eggs in clusters which elicit the formation of large composite granulomas. The worms of these two species also tend to be sedentary, remaining in a single location for prolonged periods, thus producing large focal lesions in the intestines or urinary tract. Worm pairs of these two species also are gregarious and many worm pairs are often found in a single lesion. The size of circumoval granulomas, and the degree of fibrosis, are T cell dependent. The modulation of granuloma size is largely T cell dependent in mice infected with S. mansoni but is mostly regulated by serum factors in S. japonicum infected mice. In spite of these differences in egg laying and immunoregulation both S. mansoni and S. japonicum produce Symmers' fibrosis in the chimpanzee while S. haematobium does not, despite the presence of numerous eggs in the liver.